The living and the dead; an investigation into the status of erasure within the floor of Bath Abbey. (2nd January 2016) - Littlefield, David
Abstract: The floor of Bath Abbey offers a singular test of authenticity. Nineteenth century repairs and additions caused horizontal grave markers, which comprise the majority of the Abbey's floor, to become separated from the burial sites they were intended to memorialize. A century and a half of further occupation has had the effect of removing many inscriptions as surfaces are worn smooth. The result is a patchwork of unintended edits and accidental poetry. This paper explores the notions of authenticity, essence, memorial and erasure as they pertain to the Abbey floor, in particular with regard to the role the body plays in inhabiting/eroding the floor—from both above and below. The author argues that the stones which are most out of place or worn to a state of erasure are no less authentic than their intact equivalents, but that they can be considered to have moved to another state of authenticity rich in resonance and meaning. This paper, in short, is a defense of erasure and that erosion through occupation may be considered a form of social memory; indeed, the marks of walking become the inscription. In other words, the undesigned (erasure, the cutting and repositioning of ledger stones, the missing inscriptions) becomes considered not as a form of dirt but as the positive traces of on-going and meaningful occupation.